Wirid Lathif Tradition Love and Tolerance Education in Pesantren - Hidayati, Zuhriyyah; Amar, Abu (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study explores the Wirid Lathif tradition at the Tahfidhul Qur’an Islamic Boarding School in Paciran as a form of spiritual pedagogy that shapes students’ gentleness (lathifah), love (mahabbah), and tolerance (tasamuh). Using a phenomenological qualitative approach, data were collected through observations, interviews with kiai, ustadz, and students, as well as documentation of wirid activities. The findings reveal that Wirid Lathif functions as an “inner madrasah” that educates the heart and complements intellectual learning. The repetitive and collective wirid practice cultivates spiritual calm, empathy, and humility, fostering affective transformation through daily habituation. Students experience increased patience, emotional control, and social harmony, showing that spiritual training effectively instills moral values without explicit instruction. Moreover, Wirid Lathif acts as a hidden curriculum promoting religious moderation by nurturing soft-heartedness and reflective religiosity. The study concludes that Wirid Lathif represents a model of Sufistic character education integrating spiritual, moral, and social dimensions and also relevant for developing compassionate and tolerant individuals in the context of contemporary Islamic education.